The expression fmap . fmap
has two instances of fmap
which can, in principle, have different types. So let's say their types are
fmap :: (x -> y) -> (g x -> g y)
fmap :: (u -> v) -> (f u -> f v)
Our job is to unify types (which amounts to coming up with equality relations between these type variables) so that the right-hand side of the first fmap
is the same as the left-hand side of the second fmap
. Hopefully you can see that if you set u = g x
and v = g y
you will end up with
fmap :: ( x -> y) -> ( g x -> g y )
fmap :: (g x -> g y) -> (f (g x) -> f (g y))
Now the type of compose is
(.) :: (b -> c) -> (a -> b) -> (a -> c)
To make this work out, you can pick a = x -> y
and b = g x -> g y
and c = f (g x) -> f (g y)
so that the type can be written
(.) :: ((g x -> g y) -> (f (g x) -> f (g y))) -> ((x -> y) -> (g x -> g y)) -> ((x -> y) -> (f (g x) -> f (g y)))
which is pretty unwieldy, but it's just a specialization of the original type signature for (.)
. Now you can check that everything matches up such that fmap . fmap
typechecks.
An alternative is to approach it from the opposite direction. Let's say that you have some object that has two levels of functoriality, for example
>> let x = [Just "Alice", Nothing, Just "Bob"]
and you have some function that adds bangs to any string
bang :: String -> String
bang str = str ++ "!"
You'd like to add the bang to each of the strings in x
. You can go from String -> String
to Maybe String -> Maybe String
with one level of fmap
fmap bang :: Maybe String -> Maybe String
and you can go to [Maybe String] -> [Maybe String]
with another application of fmap
fmap (fmap bang) :: [Maybe String] -> [Maybe String]
Does that do what we want?
>> fmap (fmap bang) x
[Just "Alice!", Nothing, Just "Bob!"]
Let's write a utility function, fmap2
, that takes any function f
and applies fmap
to it twice, so that we could just write fmap2 bang x
instead. That would look like this
fmap2 f x = fmap (fmap f) x
You can certainly drop the x
from both sides
fmap2 f = fmap (fmap f)
Now you realize that the pattern g (h x)
is the same as (g . h) x
so you can write
fmap2 f = (fmap . fmap) f
so you can now drop the f
from both sides
fmap2 = fmap . fmap
which is the function you were interested in. So you see that fmap . fmap
just takes a function, and applies fmap
to it twice, so that it can be lifted through two levels of functoriality.